Effect Of Ehretia Microphylla Lamk On Stimulation Of Reproductive Function And Ovarian Folliculogenesis In Rats - V. AARTHI,; J. ANBU,; K.F.H. NAZEER AHAMED,; ASHWINI ANJANA,; V.VELPANDIAN, (International Journal of Pharma and Bio Sciences, 2012)
This study has been undertaken to investigate the effect of Ehretia microphylla L._ on folliculogenesis, relative ovary and uterus weight and the number of ovarian surface follicles in female Wistar albino rats. The study consisted of 24 female wistar rats that were divided into four groups. Group-I 0.5 ml distilled water, Group II, III and IV were orally administered with powdered form of E. microphylla L and adjuvant at 500 mg/kg and 1000 mg/kg and only adjuvant (Palm jaggery)respectively. After 10 days, blood samples were taken from all groups in order to measure the serum levels of luteinizing hormone (LH), follicle stimulating hormone (FSH) and estradiol hormones. Ovaries and uterus were removed for histopathology. Significant increase in FSH, LH and estradiol levels, ovarian and uterine weight was observed along with enhanced folliculogenesis in the experimental groups. Thus results suggest significant stimulatory effect on female reproductive activity which can enhance fertility in female adult rats.